ANALYSIS OF PUBLIC SATISFACTION IN DPMPTSP NAKER OF PANGKALPINANG CITY - Devi Valeriani; Dian Prihardini Wibawa; Aning Kesuma Putri; Nanang Wahyudin (AFEBI Management and Business Review, 2018)
The quality of public service performance has a broad impact in various parts live, especially to achieve public welfare. Therefore the efforts to improve public services must be conducted continuously by  Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja (DPMPTSP NAKER) of Pangkalpinang. The Efforts to improve the quality of services must be conducted jointly, integrated, programmed, directed, and consistent by paying attention to the needs and expectations of the public, so that the services provided to the community can be given appropriately, quickly, cheaply, openly, simply and easily implemented. The purpose of the Community Satisfaction Index Survey preparation is to find out the performance of DinasPenanaman  Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja of Pangkalpinang which will be used as a basis for making and establishing policies in order to improve the quality of public services.The Survey of Community Satisfaction Index (IKM) is made refers to the provisions of  Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Republik Indonesia Number 14 Year2017 concerning Guidelines for Preparing the Community Satisfaction Survey of Public Service  Providers Units of at least 9 SKM Elements. The respondents of the survey were the people who were applying for licensing at DPMPTSP NAKER of Pangkalpinang amounted to 224 people. The Community Satisfaction Index Survey is collaborating with University of Bangka Belitung through the Institute for Research and Community Service (LPPM), which is formulated through a cooperation agreement with the service provider of Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja of Pangkalpinang.Based on the results of the IKM survey with 9 elements, obtained the value of the service element which has the lowest value is the element of Requirement (U1) with a value of 3.193 and the element that has the highest value is the Cost / Tariff (U4) of 3.767. The community satisfaction survey in the DinasPenanaman Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja of Pangkalpinang with a weighted NRR of 3.374 was converted into the public satisfaction index at a service unit of 84.36, which was categorized into B or good.Keywords: Community Satisfaction Index, Public Satisfaction, Public Service